Kemas Ulang Informasi Randai bagi Siswa di SMA 1 Koto Timur Kabupaten Padang Pariaman - Hidayat, Salfiko; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2019)
AbstractThis paper discusses the need for randai information and the process of making Randai Information Repackage for Students at SMAN 1 V Koto Timur. This study aims to determine the need for randai information and how to re-make randai information for students in SMA N 1 V Koto Timur. This study uses a descriptive method that is conducting direct interviews with a number of students at SMAN N 1 V Koto Timur, Padang Pariaman Regency. First, the need for randai information in SMAN 1 V Koto Timur, there are still some students who want to meet the general information needs both from other information such as reading materials in the library such as books and randai activities themselves. Secondly, there are several stages in making information back: (1) Identifying user needs by collecting and examining what will be contained in the information package; (2) Finding the needed sources, searching for information by collecting selected books and articles/ journals from the internet; (3) The collection of information that has been obtained from several books and articles/ journals from the internet is then stored in a computer file or flashdisk; (4) Packaging information by selecting data from various sources of books and articles/ internet journals and packaged in printed form; (5) Determine the form of information packaging to be made, namely printed; (6) Editing, checking deficiencies and forming packaging to make it more attractive and easily read by information users; (7) Printing of packaging is in the form of print publication. Third, in making information repackaging there are some obstacles. First, Constraints: (1) Data search and information gathering; (2) Lack of expertise in making packaging; (3) Determination of information to be contained in the package. Second, the efforts made: (1) Gathering as much data as possible from books, journals and other official articles; (2) Asking for help from experts to help the process of making packaging; (3) Finding information from several journals and book.Keywords: information, randai, and repackageÂ